Cultivo de dendezeiro no Pará: dinâmicas espaciais e uma aproximação geohistórica - Adriano Venturieri; Moisés Mourão Jr.; Alfredo K. O. Homma; Emeleocípio B. Andrade (Confins)
The aim was to harmonise two approaches, one based on history and the other on achievements in space. A geohistorical approach was therefore sought. Using communal production data from the PAM-IBGE series, we assessed indicators of representativeness and dominance, which indicate possible phases in the oil palm production chain. The relevance of each of these phases indicated trajectories between communes. A current assessment of these trajectories is provided. On a number of occasions, the strong presence of the state was evident, allowing the establishment of cultivation to be seen as a product of planning. Currently, the chain is highly concentrated in the micro-region of Tomé-açu, in particular Tailândia and Moju, which could be called the "palm region", although the new areas incorporated in recent years indicate a clear territorial expansion of cultivation, both in terms of consolidation and very recent production. The role of the State as initiator and guarantor of the development of the oil palm sector is assessed.